2007
DOI: 10.4049/jimmunol.178.3.1692
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of B Cell Activation in SLAM-Associated Protein-Deficient Mice Is Associated with Changes in Gammaherpesvirus Latency Reservoirs

Abstract: Signaling lymphocyte activation molecule (SLAM)-associated protein (SAP)) interactions with SLAM family proteins play important roles in immune function. SAP-deficient mice have defective B cell function, including impairment of germinal center formation, production of class-switched Ig, and development of memory B cells. B cells are the major reservoir of latency for both EBV and the homologous murine gammaherpesvirus, gammaherpesvirus 68. There is a strong association between the B cell life cycle and viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 71 publications
(87 reference statements)
1
11
0
Order By: Relevance
“…As shown in figure 1A–C, there were significantly fewer H2bYFP positive B cells in SAP-deficient mice at both doses. Consistent with previously published results [35], [36], there was also a significant reduction in the frequency of viral genome positive cells during the early establishment of latency (Fig. 1D,F).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…As shown in figure 1A–C, there were significantly fewer H2bYFP positive B cells in SAP-deficient mice at both doses. Consistent with previously published results [35], [36], there was also a significant reduction in the frequency of viral genome positive cells during the early establishment of latency (Fig. 1D,F).…”
Section: Resultssupporting
confidence: 93%
“…Since previous studies have shown that infection of SAP-deficient mice with MHV68 results in reduced viral load in spleens [35], [36], we infected mice with a recombinant MHV68 that expresses yellow fluorescent protein (MHV68-H2bYFP) [31] to compare the infected B cell populations in these mice with those seen in wild type mice. Mice were infected intranasally with either a low dose (1,000 pfu) or a high dose (4×10 5 pfu) of virus, and spleens were harvested at 16–18 days post-infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Deletion of another B7 family member, 4-1BB, impairs T cell effector function and leads to increased viral latency [38]. On the other hand, mice lacking the SLAM associated protein (SAP), a negative regulator of lymphocyte signaling, have increased CD8 + T cell activation in response to infection and impaired antibody production that ultimately does not alter long term control of the virus [39], [40]. The role of mutations that generate gain-of-function T cells in the absence of other off-target B cell effects in the control of MHV68 infection has not been determined.…”
Section: Introductionmentioning
confidence: 99%